Eudendrium tottoni Stechow 1932 ... - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
Eudendrium tottoni Stechow, 1932 (*) Eudendrium insigne — Hickson & Gravely, 1907: 7, pl. 1 fig. 4. Eudendrium ramosum — Ritchie, 1913: 12. Eudendrium antarcticum Totton, 1930: 140 –141. Eudendrium tottoni — Marques et al. 2000: 107, figs 83, 84. Remarks. Totton (1930) considered that there was only one species of Eudendrium recorded from the glacial Antarctic waters. He indicated that the species had been assigned to several species, but that it was very doubtful whether it was conspecific with any of them. Consequently, he considered it a different, new species and gave it the name of E. antarcticum, selecting as holotype a specimen assigned to E. insigne by Hickson & Gravely (1907). Stechow (1932) gave a new name, E. tottoni, to this species because E. antarcticum was a pre-occupied name (E. antarcticum Stechow, 1921). According to Marques et al. (2000), the species remains doubtful as it is ill defined and its cnidome is unknown. Distribution. In the Ross Sea, recorded from McMurdo (Hickson & ... : Published as part of ÁLVARO L. PEÑA CANTERO, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa, pp. 1-65 in Zootaxa 4293 (1) on pages 15-16, DOI: 10.11646/zootaxa.4293.1.1, http://zenodo.org/record/828475 ...